FACTORS AFFECTING THE SUSTAINABILITY DISCLOSURE IN COMPANY ANNUAL REPORT (Empirical Study on Manufacturing Companies Listed in IDX 2009-2011) - , BELLA CHYNTIARA, Taufikur Rahman, S.E., M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is conducted to determine companiesâ factors or variable affecting the disclosure of Corporate Social Responsibility (CSR) disclosure in the annual report of manufacturing companies in Indonesia. CSR is an a voluntary ethical business practices designed to share the benefits owned by company to the shareholders, employees, society and environment. The benefits is not limited to the economics but to the extend of environmental and social benefits. The main question in this reseach is what factors sustainability disclosure in the annual report. This research is conducted on manufacturing companies listed in Indonesia Stock Exchange (IDX) 2009-2011. Manufacturing companies are chosen as a sample because this industry produce a lot of finish goods and services for the society and have various direct contacts with the society and environment surround. This study examines the influence of company size, profitability and leverage on sustainability disclosure. The result of the reseach indicates that the size of the company consistently affecting the companyâs sustainability disclosure. Meanwhile, companiesâ profitability and leverage give no significant effect on company sustainability disclosure.